Fostering Emergency Preparedness Culture: Infrastructure, Training, and Promotion at SD Ummu Aiman Malang - Rifai, Ridwan Muhamad; Muhammad, Dzul Fikri; Pasaribu, Aswin; Handayani, Agil Fitri; Wulandari, Fadila Fitria (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
Safety education for elementary school students is essential for preparing them for emergencies and preventing casualties. However, SD Ummu Aiman, an elementary school in Malang with 653 students, was inadequately equipped in terms of both infrastructure and knowledge to respond effectively in emergencies. This community service initiative aimed to enhance the school’s emergency preparedness and evacuation system by providing evacuation infrastructure, conducting awareness training, simulating emergency drills, and promoting a safety culture through safety induction aimed at fostering behaviour-based safety. The awareness training resulted in an average increase in knowledge of 15.1 points among 53 teachers (p-value < 0.001), and evacuations were completed in under three minutes. It is anticipated that the knowledge and skills transferred to the teachers will be conveyed to the students, who are crucial for developing readiness for emergencies and fostering a safety-minded society in the future.